A town like Alice - Shute, Nevil, 1899-1960 (Vintage classics., 1952)
A novel told partly in flashbacks about a girl's search for the Australian she met in Malaya during World War II. A young woman who miraculously survived a Japanese "death march" in World War II, and an Australian soldier, also a prisoner of war, who offered to help her--even at the cost of his life.